Responsible Leadership and Affective Organizational Commitment: The Mediating Effect of Corporate Social Responsibility - Piñeros Espinosa, Rafael Alejandro (Frontiers in Psychology, 2022)
Organizations and their leaders are challenged to assume a responsible behavior given the increase of corporate scandals and the deterioration of employee commitment. However, relatively few studies have investigated the impact of responsible leadership (RL) on employee commitment and the effect of corporate social responsibility (CSR) in this relationship. Using the social identity theory this article examined the mediating effect of CSR practices in the relationship between RL and affective organizational commitment (AOC). Data collection was done through a paper survey completed by 309 full-time Colombian employees. Structural equation modeling was used to analyze the data. The results showed that CSR fully mediated the influence of RL on AOC. Thus, RL is an effective mechanism to develop CSR practices that in turn increase the levels of AOC of employees.